A married couple - Yanovsky, Zalman 1944-2002; Bush, Douglas ca. 20. Jh (<<The>> Criterion collection, 2010)
"An "actuality drama" about a real-life marriage in crisis, in which the couple attempts to identify and resolve the conflicts and resentments that have driven them to the brink of separation." [imdb.com]
Original: Kanada 1969
Bildformat 1.33:1
Keywords: Ehekonflikt; Film; DVD-Video